PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 18 SUNGAI PAKNING KECAMATAN BUKIT BATU - Yurtati Yurtati; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes IPS students with an average grade of 65. Among the students numbering 26 people only 5 students who completed KKM with classical completeness reached 56.53%. This research is a classroom action research (PTK) conducted aims to improve learning outcomes IPS Elementary School fifth grade students 18 Sungai Bukit BatusubdistrictPakning by applying the Cooperative Learning Model Student Team Achievement Division (STAD). Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the increase in the number of students who reach the KKM of 5 people (56.53%) on the base score, 18 (67.88%) in cycle I. In the first cycle means the class that the sample has completely classical. At the first meeting of the first cycle of teacher activity percentage is 75%, the second meeting of 79.16%. While the second cycle of the first meeting with the percentage of 83.33% and the second meeting increased 87.5%. While the student activity also increased that the first meeting of the first cycle of the percentage of student activity is 58.33% 91.66% second meeting. The first meeting of the second cycle of 87.5%, the second meeting of 95.33%. Results of the study in class V SDN 18 Pakning Sungai Bukit Batusubdistrict prove that the implementation of cooperative learning model type Student Team Achievement Division (STAD) can improve learning outcomes fifth grade students of SDN 18 Pakning Sungai Bukit Batusubdistrict. After analyzing the data the research that studies the application of the model of cooperative STAD type can improve learning outcomes IPS class V SDN 18 Sungai Pakning.Keywords: Model Contextual Teaching and Learning (CTL), IPS Learning Outcomes